Answer:
a) 4.2 m/s
b) 13.6 m/s^2
Step-by-step explanation:
She is jumping, and when her feet no longer touch the ground she is in free fall, only affected by the acceleration of gravity.
The equation for position under constant acceleration is:
Y(t) = Y0 + Vy0 * t + 1/2 * a * t^2
We set up a reference system that has its origin at the point her center of mass is when she is standing and the positive Y axis points upwards, then:
Y0 = 0 m
a = -9.81 m/s^2
The equation for speed under constant acceleration is:
V(t) = Vy0 + a * t
We know that when she reaches her highes point her vertical speed will be zero because that is wehn her movement changes direction. We'll call this moment t1.
0 = Vy0 + a * t1
a * t1 = -Vy0
t1 = -Vy0/a
If we replace this value on the position equation we can find her initial speed:
Y(t1) = Y0 - Vy0 * Vy0/a + 1/2 * a * (-Vy0/a)^2
Y(t1) = - Vy0^2/a + 1/2 * Vy0^2/a
Y(t1) = -1/2 * Vy0^2 / a
Vy0^2 = -2 * a * Y(t1)
I assume her center of mass is at half her height, so when she is standing it would be at 93 cm of the grouind, and when she is crouching at 46.5 cm.
Therefore when she jumps her centr of mass moves 0.465 m before leaving the ground.
During that trajectory she moves with acceleration.
Y(t) = Y0 + Vy0 * t + 1/2 * a *t^2
In this case her initial position is
Y0 = -0.465
Her initial speed is
Vy0 = 0
At t=t0 her position will be zero
The equation for speed under constan acceleration is
Vy(t) = Vy0 + a * t
Her speed at t0 will be 4.2 m/s
4.2 = a * t0
t0 = 4.2 / a
0 = -0.465 - 1/2 * 9.81 * (4.2 / a)^2
0.465 = 4.9 * 17.6 / a^2
a^2 = 86.2 / 0.465